Biorecognition of hydrogen peroxide using a novel electrochemical platform designed with Glossoscolex paulistus giant hemoglobin - Nascimento, Evair D.; Abrantes-Coutinho, Vanessa E.; Oliveira, Thiago M. B. F.; Santiago, Patrícia S. [UNESP]; Carvalho, Francisco A. O. (Springer Nature, 2022)
The giant extracellular hemoglobin of the annelid Glossoscolex paulistus (HbGp; 3.6 MDa) is a valuable and underexplored supramolecular hemoprotein system for the biorecognition of reactive oxygen species. In this work, an efficient and simple electrochemical platform was designed for analyzing H2O2, using HbGp covalently immobilized on Nafion®-modified glassy carbon electrode, named as HbGp/Nafion/GCE. Voltammetric and spectroscopic studies revealed the importance of prior modification of the electrodic support with the conducting polymer to obtain satisfactory hemoglobin electroactivity, as well as a biocompatible microenvironment for its immobilization. In terms of biological activity, it was observed a greater reactivity of the biomolecule in acidic medium, enabling the detection of the analyte by a quasi-reversible mechanism, whose kinetics was limited by analyte diffusion. In the presence of H2O2, the native structure of hemoglobin (oxy-HbGp (Fe2+)) oxidizes to ferryl-HbGp (Fe4+) and this redox reaction can be monitored on HbGp/Nafion/GCE with a detection limit of 8.5 × 10‒7 mol L-1. In addition to high sensitivity, the electrochemical biosensor also provided reproducible, consistent, and accurate measurements. The electroanalytical method showed an appropriate performance to quantify different levels of H2O2 in milk samples, proving the potential of HbGp/Nafion/GCE for this purpose. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Electroanalysis; Electrochemical biosensors; Giant hemoglobins; Glossoscolex paulistus; H2O2